Analisis studi kelayakan bisnis pada usaha mikro kecil dan menengah ditinjau dari aspek pasar dan pemasaran: Studi kasus pawon tambun di kota malang - Cahyati, Dwi Nur (Maliki Interdisciplinary Journal, 2025)
This study aims to assess the feasibility of the Pawon Tambun business located in Lowokwaru, Malang City from the aspects of market and marketing. This study uses a qualitative data collection approach through interviews, observations, and documentation. Based on the findings on the market and marketing aspects, Pawon Tambun is worthy of development. This study found that Pawon Tambun has great market potential, especially with its strategic location in Malang City and a delivery system that makes it easy to access outside the city. To maintain business sustainability, it is recommended that Pawon Tambun continue to develop a digitalization strategy and strengthen the quality of services and products offered. In addition, collaboration with local MSMEs and the use of social media as a means of promotion are considered important to increase business visibility and competitiveness. By combining adaptive and innovative marketing strategies, Pawon Tambun has the opportunity to become one of the leading culinary entrepreneurs in Malang City and its surroundings.